Emergence of HCV genotype 6 and its new variants among intravenous drug users in Manipur, a north-eastern state of India - Raina Das; Supradip Dutta; Sagnik Bakshi; Aritra Biswas; Shreyasi Nath; Moumita Majumdar; Priya Verma; Upasana Baskey; Shanta Dutta; Provash Chandra Sadhukhan (Therapeutic Advances in Infectious Disease)
Background: Manipur, a north-eastern state of India, has a high incidence of intravenous drug use with an equally high prevalence of Hepatitis C virus (HCV) infection. Objectives: This cross-sectional study aimed to evaluate the impact of certain risk factors enhancing the susceptibility of acquiring HCV. Design: A total of 1008 participants from various risk groups, from nine districts across the state, were enrolled. Blood samples along with demographic data were collected from the study participants. Methods: HCV RNA was isolated and nested RT-PCR was performed followed by Sanger sequencing for genotyping. Phylogenetic and phylogeographic studies were further conducted. Results: Of the total, 493 (48.90%) samples were HCV sero-reactive. Among the sero-reactive samples, 406 (82.35%) were HCV RNA positive. In case of the subgroup PWID + HIV, sero-reactivity (82.22%) and viremia (90.54%) were observed to be exceptionally high. It was noted that HCV sero-reactivity increased four times in people living with HIV (PLHIV) who continued to inject drugs. Three HCV genotypes and eight subtypes were circulating in this study population. Conclusion: In PLHIV who continued to inject drugs, HCV sero-reactivity increased four-fold. About 40% of the population living with HCV belonged to genotype 6, while genotype 1 showed a noticeable decline. Phylogeographic analyses and spatiotemporal reconstructions revealed that most of the subtypes migrated from far south-east Asian countries like Thailand, Malaysia, Myanmar, and Singapore.